Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1001/jamanetworkopen.2019.4270
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Life Purpose and Mortality Among US Adults Older Than 50 Years

Abstract: Key Points Question Does an association exist between life purpose and all-cause or cause-specific mortality among people older than 50 years participating in the US Health and Retirement Study? Findings This cohort study of 6985 adults showed that life purpose was significantly associated with all-cause mortality. Meaning Life purpose is a modifiable risk factor and as such the role of interventions to improve life purpose shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 38 publications
1
100
0
3
Order By: Relevance
“…Loneliness and a lack of occupation may lead to the loss of the life purpose which is a key element to activate elderly individuals. It has been shown that a stronger purpose in life among subjects over 50 years is associated with a decreased all-cause and some cause-specific mortality (25). Purposeful living may potentially improve both social and psychological domains of individual's functioning, and thus, this should be a task for community-based senior organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness and a lack of occupation may lead to the loss of the life purpose which is a key element to activate elderly individuals. It has been shown that a stronger purpose in life among subjects over 50 years is associated with a decreased all-cause and some cause-specific mortality (25). Purposeful living may potentially improve both social and psychological domains of individual's functioning, and thus, this should be a task for community-based senior organizations.…”
Section: Discussionmentioning
confidence: 99%
“…They also show higher degrees of self-compassion, self-efficacy, and resilience ( 33 , 43 ). Meaningfulness is robustly associated with lower mental distress ( 36 , 43 47 ), higher physical health ( 48 – 51 ), and lower mortality risk ( 49 , 50 , 52 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, eudaimonic theories, such as Psychological Wellbeing theory (PWB; Ryff, 1995), emphasise purpose and meaning in life. Intriguingly, recent epidemiological research on the United States Health and Retirement Study has identified associations between stronger life purpose and lower mortality (Alimujiang et al, 2019), highlighting an intimate connection between mental wellbeing and physical health. Ryff (1995) proposed six components of PWB which include; self-acceptance, positive relationships with others, autonomy, personal growth, environmental mastery and purpose in life.…”
Section: Introductionmentioning
confidence: 99%